DEVELOPMENT OF HELPLESSNESS SCALE ON THE WORKPLACE (Journal of Medical & Health Sciences Review, 2025)
Nearly one-third of your life is devoted to your job. Your employee's satisfaction and fulfilment at work will naturally show in his whole personality and personal growth. The benefits of a pleasant workplace extend far beyond increased output and contentment on the part of workers. But if the of workplace is toxic, the employee may feel helpless, stress, anxiety etc. these feelings lead to depression and also affect the working of employee. Helplessness is one of the major issue at workplace.  To environment determine the helplessness, we required the tools to measure it. The current investigation was undertaken to examine the phenomenon of helplessness within the workplace environment. At first, a pool of   8 items were originated for   interview of major professions (Doctors/ paramedical staff / health professionals, Lawyers, Engineers, Teachers, Architects, Bankers) in  Pakistan. By the help of interviews, a pool of 81 items were created first that undergoes the expert PHD SCHOLAR’S examination, from the 81 items 37 were modified and 8 items were deleted. By the expert’s evaluation, a pool of 58 items were added. So the total pool of items was now 131. When all 131 items were testified by the 5 PHD Scholar (Expert Evaluation), the next step was to generate the Google form. The pilot study was done with 131 items to the 107 professionals of workplace.  Further, field administration of these items was done above 467 participants by using Google Form. The 91 items were conducted on 467 respondents. The data was examined by using exploratory and confirmatory factor analysis and reliability test. Hence, at the end 41 items were reliable to use. While preceding literature also aligned that appropriate number of items are at least 4 to 6 required for conceptual dimensions. The full scale reliability was .959.  It shows high reliability.